El sentido en cuidadores de pacientes en hemodiálisis. Un estudio fenomenológico - Herrera Bernal, Daniela (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Due to the high impact of chronic kidney disease worldwide, the number of caregivers of these patients is also increasing. Since it is a disease with a long progression in time, it is demanding and exhausting for the caregiver; therefore, it is necessary to address the experiences of the caregiver. The current research was carried out in the hemodialysis unit of the Hospital General "Dr. Miguel Silva", Morelia, Michoacán. The aim was to explore the sense of caregiving in caregivers of patients undergoing hemodialysis treatment. It corresponds to a single case study with phenomenological design. The semi-structured interview, the observation, the Stress Coping Questionnaire and the phenomenological interview were used to collect information. Giorgi's descriptive phenomenological psychological method was used as an analytical strategy. The results obtained show a predominance of female caregivers and a family bond with the patient. The caregiver restructures her daily routine according to the demands of caregiving, assuming the entire burden of care, so that support networks are used only in case of emergency and symptoms of overload. The role is seen as a responsibility and a moral commitment to be fulfilled above personal care, an aspect that is related to Mexican culture with respect to the construction of gender and family historically taught and learned. Religion (RLG, for its acronym in Spanish) and Focus on Problem Solving (FSP, for its acronym in Spanish) are the most commonly used coping strategies, due to the strong religious component in Mexico and the urgency that the caregiving process demands. However, the experience of caregiving has allowed it to enrich these strategies. The private sector continues to be the primary service for hemodialysis coverage in the face of an insufficient Mexican health system.

Debido al alto impacto a nivel mundial de la Enfermedad Renal Crónica, el aumento en el número de cuidadores de estos pacientes es igualmente creciente. Dado que es un padecimiento de progresión larga en el tiempo resulta demandante y desgastante para quien cuida; por lo que es preciso abordar las experiencias del cuidador. La presente investigación se efectuó en la unidad de hemodiálisis del Hospital General “Dr. Miguel Silva”, Morelia, Michoacán. El objetivo fue explorar el sentido del cuidado en cuidadores de pacientes en tratamiento hemodialítico. Corresponde a un estudio de caso único con diseño fenomenológico. Se utilizaron la entrevista semiestructurada, la observación, el Cuestionario de Afrontamiento del Estrés y la entrevista fenomenológica para la recolección de información. Como estrategia analítica se empleó el método psicológico fenomenológico descriptivo (Giorgi & Giorgi, 2003). Los resultados obtenidos muestran en el cuidado un predominio del sexo femenino y vínculo familiar con su paciente. La cuidadora reestructura su rutina diaria de acuerdo con las exigencias del cuidado, asumiendo toda la carga de este, por lo que las redes de apoyo son usadas únicamente en caso de emergencia y ante síntomas de sobrecarga. El rol es visto como una responsabilidad y un compromiso moral a cumplirse por encima del cuidado personal, aspecto que guarda relación con la cultura mexicana respecto a la construcción de género y familia históricamente enseñados y aprendidos. La Religión (RLG) y la Focalización en la Solución del Problema (FSP) son las estrategias de afrontamiento más utilizadas, por el fuerte componente religioso en México y la urgencia que exige el proceso de cuidar. No obstante, la experiencia de cuidado le ha permitido enriquecer dichas estrategias. El sector privado continúa siento el servicio primario para la cobertura de la hemodiálisis ante un insuficiente sistema de salud mexicano.
Facultad de Psicología. Maestría en Psicología
Keywords: info:eu-repo/classification/cti/5; FP-M-2025-0089; Cuidador principal; Hemodiálisis; Estrategias de cuidado; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19229